PHYSICAL-CHEMICAL ASSESSMENTS OF GOURAMI(Osphronemus goramy) FISH CRACKERS PREFERRED BY CONSUMERS - Baharu Simanjuntak; Desmelati Desmelati; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to determine the physical-chemical assessments of crackers added with different gourami meat and to determine crackers preferred by consumers. The method used was an experimental method using a non factorial Complete Randomized Design (CRD) with 3 levels of treatment, namely: H1 (100 g gourami meat), H2 (150 g gourami meat), and H3 (200 g gourami meat). The analysis parameters observed were sensory / consumer acceptance (appearance, aroma, taste, and texture), the ability to swell, and chemical properties (moisture, ash, protein, and fat). Based on this study, 200 g (H3) gourami meat was the best crackers / favored by 76 panelists (95%) consumers with yellowish-white appearance characteristics (3.75), specific fish flavor and meat aroma (3.73), fishy taste (3.43), crispy, chewy, and dense texture (2.75). While, the chemical properties were moisture3.85%moisture content, 2.00% ash content, 3.85% fat content, 11.13% protein content, and the ability to swell of 325.80%.Keywords: Gourami, fish crackers,physical and chemical properties, the ability to swell